2019
DOI: 10.1007/s10584-018-02364-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety nets and natural disaster mitigation: evidence from cyclone Phailin in Odisha

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The results are also consistent with a recent evidence synthesis on women's groups and covariate shocks (such as drought, floods, or conflict‐related shocks), which found that households with exposure to women's groups had lower food insecurity, higher consumption, and higher income after weather shocks, compared to other households (Walcott et al, 2021; Demont, 2022; Christian et al, 2019; Karlan, Savonitto, Thuysbaert, & Udry, 2017; Wineman et al, 2017). While SHGs may help members absorb some shocks, group membership seldom fully mitigates the effect of the shock.…”
Section: Discussionsupporting
confidence: 89%
“…The results are also consistent with a recent evidence synthesis on women's groups and covariate shocks (such as drought, floods, or conflict‐related shocks), which found that households with exposure to women's groups had lower food insecurity, higher consumption, and higher income after weather shocks, compared to other households (Walcott et al, 2021; Demont, 2022; Christian et al, 2019; Karlan, Savonitto, Thuysbaert, & Udry, 2017; Wineman et al, 2017). While SHGs may help members absorb some shocks, group membership seldom fully mitigates the effect of the shock.…”
Section: Discussionsupporting
confidence: 89%
“…Geographical setting and PHE Open access Open access on microfinance interventions and financial aid (one cross-sectional, one case-control and one experimental study), [56][57][58] and one cross-sectional study evaluated uptake of a food aid programme implemented in response to several major droughts in Ethiopia. 59 The fifth study, a randomised controlled trial conducted by Bandiera et al, assessed the impact of a multicomponent intervention for young women and girls (aged 12-25 years) in the context of Ebola, featuring training on financial literacy and vocational skills, access to microfinance and other noneconomic programme components.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…63 Two studies reported on dimensions of equal opportunities, specifically capturing girls' school enrolment, their numeracy and literacy levels, and the engagement of school-aged girls in income-generation activities (which can hamper their educational achievements), 31 as well as women's civic and political engagement. 71 Lastly, two studies assessed interventions on women's access to economic resources, specifically food aid membership uptake, 59 female employment, 69 and girls' financial literacy and entrepreneurial confidence, 31 and two studies focused on genderbased violence. 31 58 Figure 2 Geographical scope and intervention types of included studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations